Analisis Dampak Penggunaan Internet Terhadap Perilaku Peserta Didik Kelas VIII Di MTs Muhammadiyah Wuring - Marwah, Marwah (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2022)
ABSTRAK This research is motivated by the widespread use of the internet among students. So that with that use they are free to access unlimited ideas and information, it can directly affect andhave, a positive or negative impact. Thus, this study aims to determine the impact of Internet use on the behavior of Class VIII Bstudents at MTs Muhammadiyah Wuring. This type of research is a field research in the form of qualitativedescriptive. This research was carried out at MTs Muhammadiyah Wuring. The results of this study found that the use of the internetFacebook, WhatsApp, Tiktok, Online Games, Google was the most frequently used of the five types of internet, namely tiktok and online games. Then the impact of its use consists of two namely positive impacts and negative. impacts. the positive impact is increasing insight and knowledge, becoming a communication medium, the internet as a means of business learning, a learning tool. while the negative impacts for students who use the internet is that it is easy to find things the smell like pomography, don’t care about friends environment, waste, interfere withhealth, reduce study time, cause addiction. efforts to overcome negative behavior towards internet use, namely students are considered not to be able to manage time to use the internet, parents want their children to use the internet which is useful, not to open things that are not important, unnatural student behavior can cause worries from parents of students who The negative impact of the internet can be overcome by embedding religious values, raise awareness, of adolescents, the role of increasing discipline. Finally, after seeing this tangible evidence, the writer recommends teenagers to increase their self-awareness and instill religious values.